ANALISIS PRODUKSI DAN PENDAPATAN USAHATANI KAKAO DI DESA LAIS KECAMATAN DONDO KABUPATEN TOLITOLI - Masna, Masna; Kassa, Saharia; Tangkesalu, Dance (AGROTEKBIS, 2018)
Lais Village is one of the cocoa producing regions in Dondo Sub-district Tolitoli Regency. Cocoa is one of the plantation commodities has an important role for national economy. The role is the provision of jobs, sources of income and foreign exchange country. Cocoa farming in Lais Village, Dondo sub-district, Tolitoli Regency is a source of farmers income. The purpose of this research is to know the factors that influence cocoa production, to know the income received from the cocoa farming in Lais Village, Dondo sub-district, Tolitoli Regency. This research was conducted from December 2016 to January 2017 at Lais Village, Dondo Sub-district, Tolitoli Regency, the location of the research was conducted in purposive sampling, the respondents determination was done by using Slovin formula where the number of respondents specified in this research were 33 people. The analysis tools used in this research were Cobb-Douglass production factor analysis and Revenue analysis. The results showed that the analysis of observed factors such as land area, number of plants production, had real effect, while the amount of labor, the use of fertilizer, and the use of pesticide had no significant effect on cocoa production. The average received income by cocoa farmers in Lais Village, Dondo sub-district, Tolitoli regency is Rp 12.447.368/1.37 ha/year. Keywords: Cocoa Farming, Income, Production.